Banks’ Profitability in the Period of Low and Negative Interest Rates - Calheiros de Figueiredo Dias Gonçalves, Mariana; Witzany, Jiří, 1966-; Teplý, Petr, 1977-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
In the financial landscape of the Euro Area, the role and profitability of banks are influenced by unconventional monetary policies and market changes. This study analyzes the impact of low and negative interest rates on banks' profitability indicators, specifically net interest margin (NIM), return on assets (ROA) and return on equity (ROE). Utilizing data from 2690 banks from 2004 to 2024, a linear regression is used to draw the conclusion that low or negative interest rates do not mean lower bank profitability. Moreover, the analysis of market concentration shows that in countries with significant market concentration there is a positive correlation between profitability and market concentration. The results provide important information for stakeholders, emphasizing how difficult it is for banks to be profitable in the context of continuous changing monetary policies and market conditions.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses